2015
DOI: 10.1080/13691058.2015.1043144
|View full text |Cite
|
Sign up to set email alerts
|

‘Women now wear trousers’: men's perceptions of family planning in the context of changing gender relations in western Kenya

Abstract: Gender inequity has been closely linked with unmet need for family planning among women in sub-Saharan Africa but the factors related to male family planning disapproval are not well-understood. This qualitative study explored men's perspectives of gender roles and cultural norms as they pertain to family planning. Twelve small group meetings were held with 106 married men in Nyanza Province, Kenya. Shifting gender relations made the definitions of manhood more tenuous than ever. Men's previous identities as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 29 publications
7
34
1
Order By: Relevance
“…We also found that some men reported a reduction in perpetuating sexual coercion and/or weaker adherence to normative assumptions that men have a right to sexual access to women’s bodies and that women do not have a right to refuse sex. This is an important finding given that such sexual norms have been observed by other scholars in this region of Kenya (Hatcher et al, 2013; Withers et al, 2015). …”
Section: Discussionsupporting
confidence: 80%
“…We also found that some men reported a reduction in perpetuating sexual coercion and/or weaker adherence to normative assumptions that men have a right to sexual access to women’s bodies and that women do not have a right to refuse sex. This is an important finding given that such sexual norms have been observed by other scholars in this region of Kenya (Hatcher et al, 2013; Withers et al, 2015). …”
Section: Discussionsupporting
confidence: 80%
“…It was asserted that being in such a position potentially gives women the power to make decisions about the welfare of the children, without involving their partners. Kenya's 2010 constitution recognises the role of women as key players in the political and social-economic sphere, which has led to an increase in women's participation in the workforce, and subsequent financial contributions to the household [24,25]. Previously men's identities as sole breadwinners gave them immense control over decision-making within their families; an authority that is increasingly being undermined by their wives [25].…”
Section: Discussionmentioning
confidence: 99%
“…Kenya's 2010 constitution recognises the role of women as key players in the political and social-economic sphere, which has led to an increase in women's participation in the workforce, and subsequent financial contributions to the household [24,25]. Previously men's identities as sole breadwinners gave them immense control over decision-making within their families; an authority that is increasingly being undermined by their wives [25]. Rapidly shifting gender relations made men in this study unsure about their authority to challenge and firmly oppose the practice of FGM/C within the family.…”
Section: Discussionmentioning
confidence: 99%
“…Gender and social norms play a key role in the decision to use or not to use contraception, with men playing a greater part in this decision [21, 22]. In particular, the views and perceptions of the husband/partner are key in determining contraceptive use [23–26].…”
Section: Introductionmentioning
confidence: 99%